THE EFFECT OF USING EXPOSITORY LEARNING STRATEGY ON STUDENTS’ WRITING HORTATORY EXPOSITION TEXT ABILITY (A Study at the XI Grade Students of SMA Negeri 1 Sayur Matinggi in 2018/2019 Academic Year) - NUR JANNAH (JURNAL LINER (Language Intelligence and Educational Research), 2019)
Abstract The aim of this research is to find out: 1) The extent of the application description of using expository learning strategy on students’ writing hortatory exposition text ability, 2) The extent of the students’ writing hortatory exposition text ability before and after using expository learning strategy, and 3) Whether there is any significant effect of using expository learning strategy on students’ writing hortatory exposition text ability. The population of this research is all the XI grade students that consist of 98 students. This study is carried on by using experimental method. The data is collected by the test. The writer uses statistic processes in analyzing data by using formula of ttest. After collecting the data, it is found that the application of using expository learning strategy on students’ writing hortatory exposition text ability is 3.5. It is categorized “Very Good”. The students’ writing hortatory exposition text ability before using expository learning strategy is 75.42. It is categorized “Good”. The students’ writing hortatory exposition text ability after using expository learning strategy is 86.46. It is categorized “Very Good”. The calculation of ttest formula is 7.03, meanwhile the score of the ttable 5% significant level is 2.07. It is found that t0 calculation is bigger than ttable (7.03 > 2.07). It means that there is a significant effect of using expository learning strategy on students’ writing hortatory exposition text ability at the XI grade students of SMA Negeri 1 Sayur Matinggi. Therefore, Ha is accepted. Keywords: Expository Learning, Strategy, Writing, Ability, Hortatory Exposition.